13th International Conference on Ubiquitous Computing and Ambient ‪Intelligence UCAmI 2019‬ 2019
DOI: 10.3390/proceedings2019031057
|View full text |Cite
|
Sign up to set email alerts
|

Smart Education: A Review and Future Research Directions

Abstract: Research and development often move forward based on buzzwords. New terms are coined to summarize new developments, often with several interpretations and without a formal definition. The term Smart Education has been coined to represent a move forward in technology-enhanced education, but what is behind it? Does it represent something essentially different from the educational technologies used before? In this paper, we do a systematic literature review to understand how this term is used, what the technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 58 publications
0
12
0
2
Order By: Relevance
“…This is a fairly recent field of research and, thus, there are some challenges linked to smart education that need further study. According to Martín, Alario-Hoyos and Kloos [196], some of these challenges are linked to connectivity, with the possibility and speed of communication; security and privacy of data; prediction systems that enable the adoption of successful corrective measures for the success of the learning process; and efficiency in the data visualization of both teachers and students.…”
Section: Ecological and Economic Added Valuementioning
confidence: 99%
“…This is a fairly recent field of research and, thus, there are some challenges linked to smart education that need further study. According to Martín, Alario-Hoyos and Kloos [196], some of these challenges are linked to connectivity, with the possibility and speed of communication; security and privacy of data; prediction systems that enable the adoption of successful corrective measures for the success of the learning process; and efficiency in the data visualization of both teachers and students.…”
Section: Ecological and Economic Added Valuementioning
confidence: 99%
“…As time passes, there is a growing number of papers published on the subject, noting the papers published in 2019 refer only to the first nine months. In so doing, since there is no formal definition for SE, much remains to be researched [26].…”
Section: Smart Education's Backgroundmentioning
confidence: 99%
“…Given the dimensions noted by [4,17], it has been observed that there is mounting literature presented on the smart learning environment (SLE) and smart pedagogy dimensions. The reviewed literature focused on the historical background of the SLE, environment's design, the technology available, the pedagogy applied, students' behavior, and perception towards such an environment [19,26]. Firstly, a brief synopsis of the historical backdrop of SLE shows that it began in the 20th century in Educational Psychology with behavioral psychologists who used conditioning to explain behavioral adaptation.…”
Section: Smart Education's Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The following are the various attributes discussed in the review such as education facilities, Technological Advancements with industry tie-up and most importantly research. Martín et al (2019)carried out various literature works on smart education (Education 4.0). Smart education means moving the technology in forward direction with lot of hope in improving the quality of education systems.…”
Section: Review Of Education 4 0 Towards National Levelmentioning
confidence: 99%